Activation reduction following an eccentric contraction impairs torque steadiness in the isometric steady-state - Nicole Mazara; Adam J. Hess; Jackey Chen; Geoffrey A. Power (Elsevier, 2018)
Background: The isometric steady-state following active lengthening is associated with greater torque production and lower activation, as measured by electromyographic activity (EMG), in comparison with a purely isometric contraction (ISO) at the same joint angle. This phenomenon is termed residual force enhancement (RFE). While there has been a great deal of research investigating the basic mechanisms of RFE, little work has been performed to understand the everyday relevance of RFE. The purpose of this study was to investigate whether neuromuscular control strategies differ between ISO and RFE by measuring torque steadiness of the human ankle plantar flexors. Methods: Following ISO maximal voluntary contractions in 12 males (25 ± 4 years), an active lengthening contraction was performed at 15°/s over a 30° ankle excursion, ending at the same joint angle as ISO (5° dorsiflexion; RFE). Surface EMG of the tibialis anterior and soleus muscles was recorded during all tasks. Torque steadiness was determined as the standard deviation (SD) and coefficient of variation (CV) of the torque trace in the ISO and RFE condition during activation-matching (20% and 60% integrated EMG) and torque-matching (20% and 60% maximal voluntary contraction) experiments. Two-tailed, paired t tests were used, within subjects, to determine the presence of RFE/activation reduction (AR) and whether there was a difference in torque steadiness between ISO and RFE conditions. Results: During the maximal and submaximal conditions, there was 5%-9% RFE with a 9%-11% AR (p < 0.05), respectively, with no difference in antagonist coactivation between RFE and ISO (p > 0.05). There were no differences in SD and CV of the torque trace for the 20% and 60% activation-matching or the 60% and maximal torque-matching trials in either the RFE or ISO condition (p > 0.05). During the 20% torque-matching trial, there were ∼37% higher values for SD and CV in the RFE as compared with the ISO condition (p < 0.05). A significant moderate-to-strong negative relationship was identified between the reduction in torque steadiness following active lengthening and the accompanying AR (p < 0.05). Conclusion: It appears that while the RFE-associated AR provides some improved neuromuscular economy, this comes at the cost of increased torque fluctuations in the isometric steady-state following active lengthening during submaximal contractions. Keywords: Eccentric, Force steadiness, History dependence, Residual force enhancement, Tremor